2018
DOI: 10.1101/433706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NetTCR: sequence-based prediction of TCR binding to peptide-MHC complexes using convolutional neural networks

Abstract: Predicting epitopes recognized by cytotoxic T cells has been a long standing challenge within the field of immuno-and bioinformatics. While reliable predictions of peptide binding are available for most Major Histocompatibility Complex class I (MHCI) alleles, prediction models of T cell receptor (TCR) interactions with MHC class I-peptide complexes remain poor due to the limited amount of available training data. Recent next generation sequencing projects have however generated a considerable amount of data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(146 citation statements)
references
References 43 publications
4
142
0
Order By: Relevance
“…However, recent studies have shown that while generic TCR-epitope prediction models can achieve a reasonable performance on interactions that involve epitopes already encountered training, they cannot yet reliable extrapolate to novel epitopes (i.e. epitope-agnostic models) (15,20). This is likely caused by the large heterogeneity in potential TCR and epitope sequences, and the limited amount of readily available training data that covers this sequence space.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that while generic TCR-epitope prediction models can achieve a reasonable performance on interactions that involve epitopes already encountered training, they cannot yet reliable extrapolate to novel epitopes (i.e. epitope-agnostic models) (15,20). This is likely caused by the large heterogeneity in potential TCR and epitope sequences, and the limited amount of readily available training data that covers this sequence space.…”
Section: Introductionmentioning
confidence: 99%
“…We can also introduce pretraining to mimic and analyze the thymic selection [56]. Furthermore, if comprehensive quantitative data on the interactions between antigens and Th clones are obtained by future measurement technologies [57][58][59][60], we can include that information on the weights of the network.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…ERGO is based on LSTM networks to encode sequential data. Previous models by Jurtz et al (18) used convolutional neural networks (CNN) for the similar task. While CNN are good at extracting position-invariant features, RNN (in particular LSTM) can catch a global representation of a sequence, in various NLP tasks (36).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we compared ERGO's performance in a mixed setting of TCRs of unknownspecificities recently proposed by Jurtz et al (18), who used a convolutional neural network (CNN) based model, NetTCR, for predicting binding probability of TCR-HLA-A*02:01 restricted peptide pairs. Jurtz et al experimented on two datasets, one downloaded from IEDB was used to train the model and an additional dataset, generated using the MIRA assay provided by Klinger et al (30), was used for evaluating the model, by testing the model performance on shared IEDB and MIRA peptides ( Table 2 and Table 3) Table 2).…”
Section: Ergo's Performance On Tcrs Of Unknown Specificitiesmentioning
confidence: 99%
See 1 more Smart Citation